2017
DOI: 10.1007/s11230-017-9770-0
|View full text |Cite
|
Sign up to set email alerts
|

Neocosmocercella fisherae n. sp. (Nematoda: Cosmocercidae), a parasite of the large intestine of Phyllomedusa bicolor (Boddaert) (Anura: Phyllomedusidae) from the Brazilian Amazon

Abstract: Neocosmocercella fisherae n. sp. is the first nematode species found parasitising Phyllomedusa bicolor from the Brazilian Amazon Region. The new species has a triangular oral opening, with bi-lobed lips, and is distinguished from N. bakeri (triangular oral opening with simple lips), and from N. paraguayensis (hexagonal oral opening with bi-lobed lips). Additionally, the new species has ciliated cephalic papillae, which are absent in the other species of the genus. The reduced uterine sac and the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Two genera of nematodes, Cosmocercella and Neocosmocercella, were specific to one family of amphibians, Phyllomedusidae, and, so far, have been reported in the HC, the Pantanal and the Amazon [23,146,147]. For a long time, the genus Schrankiana was only reported in leptodactylid amphibians [33,148], but recent studies found species of this genus parasitizing phyllomedusine frogs in the Pantanal [23].…”
Section: Richness Of Nematode Parasites and Geographical Distributionmentioning
confidence: 99%
“…Two genera of nematodes, Cosmocercella and Neocosmocercella, were specific to one family of amphibians, Phyllomedusidae, and, so far, have been reported in the HC, the Pantanal and the Amazon [23,146,147]. For a long time, the genus Schrankiana was only reported in leptodactylid amphibians [33,148], but recent studies found species of this genus parasitizing phyllomedusine frogs in the Pantanal [23].…”
Section: Richness Of Nematode Parasites and Geographical Distributionmentioning
confidence: 99%